Pewne Problemy Statyki Płyt Siatkowych - Bojda, K.H. (Engineering Transactions, 1972)
In the paper given is the solution of the boundary value problem of the lattice plates theory for a homogeneous strip loaded by arbitrary transverse load and clamped along the edges. The equations are also derived for continuous plates supported on several elastic supports. The problems have been solved by means of the Mikusiński operator.